Effect of protein-energy supplementation on in situ rumen degradability of NDF and OM of star grass (Cynodon nlemfuensis) in buffalo calves (Bubalus bubalis) - L?pez, Jos? Ra?l; El?as, Arabel; Delgado, Denia; G?nz?lez, R.; Sarduy, Luc?a; Dom?nguez, Marbelis (Cuban Journal of Agricultural Science, 2011)
Four male buffalo calves (Bubalus bubalis) of the Bufalipso breed were used to evaluate the effect of the supplementation with different amounts of protein-energy concentrate on the in situ rumen microbial degradation of NDF and OM of star grass forage. The animals had 175 ? 5 kg of liveweight and were fitted with rumen cannula, according to 4 x 4 Latin square design. Four treatments were used with different amounts of energy-protein supplementation in the diet: 0 (control), 3, 6, and 9 g kg LW-1, given once a day. The rumen degradation of the NDF and the OM of the forage showed the highest values (P < 0.05) with the rise of the incubation time for the treatments with protein-energy supplementation compared with the control, since 24 h. The supplementation had effect on the increment of the degradation rate of the NDF (0.018, 0.027, 0.029 and 0.030 fraction h-1) and on the decline of the colonization time or lag phase (2.8, 2.2, 2.1, 2.0 h) for the treatments with 0, 3, 6, and 9 g kg LW-1, respectively, whereas the degradation rate of the OM was higher in the treatments with supplementation (2.8, 2.6, 2.2) for 9, 6, 3 g kg LW-1 compared with the treatment without supplementation (1.9). The effective degradability of the forage for the NDF and the OM was higher in the treatments with supplementation compared with the control. Equations of multiple regression were established permitting to describe the process of degradation of DM, NDF, and OM with the NDF N-1 consumed ratio in the diet and the time (t) in rumen. The results prove the positive effect of the supplementation with increasing amounts of concentrate up to 9 g kg LW-1 in the diet of buffalo calves fed star grass. This could contribute to the rise in the productive activity of the buffalo calves in current rearing conditions. Key words: buffalo calves, rumen degradability, supplementation.